An efficient and cost-effective methods framework for performing biomechanical analysis on cadaveric skeletal muscle - Jay J. Byrd; Ethan L. Snow (Translational Research in Anatomy)
Introduction: The structure and arrangement of skeletal muscle fibers is the primary determinant of muscle function. While analysis of morphologic parameters to elucidate muscle structure-function relationships dates to the 17th century, considerable variability in methodology and technique to quantify these relationships exists within the literature. Additionally, applications to assess the impact of non-typical musculoskeletal morphologies on structure-function relationships are limited. This study aims to assemble and present a practical, step-by-step framework of combined methods and techniques for efficiently analyzing biomechanical impacts of cadaveric skeletal muscles. Methods: Existing skeletal muscle biomechanical formulas and experimentally determined parameters for typical fast-acting skeletal muscle were identified in the literature. The methods framework was assembled as a stepwise protocol that includes mathematical formulas, referenced accepted values, optional steps, section breaks, suggested techniques, important notes and footnotes, and materials needed for collecting necessary measurements. Proof of concept was achieved with primary histological data and imaging, along with references to examples where the methods have been successfully applied. Results: The assembled framework presents an ordered process for measuring skeletal muscle parameters, calculating the maximal isometric force of a skeletal muscle, and applying that data to understand musculoskeletal mechanics. Histology data, imaging, and a summary of studies that have successfully applied the framework methods provide visual aids and validation for the methods. Conclusions: This study presents an efficient and convenient framework of combined methods and techniques for investigators to evaluate the biomechanical impact of skeletal muscles. The practical use of this framework should optimize project efficiency and spending, increase study rigor, and minimize procedural variation across different studies. This report may serve as a foundational resource for researchers studying cadaveric muscle biomechanics, and its use especially adds translational clinical value to case analyses of non-typical musculoskeletal morphologies.